Exploration of Consensus Construction in News Practice in the Social Media Era - Yang, Kaixiang; Bexci, Manual Selvaraj (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
The construction of news consensus is based on three pillars: practical foundation, ideological preparation, and goal orientation. For news practice, its formation plays a key role in promoting the daily operation and standardization of news work. This article deeply analyzes the phenomenon of news consensus in news practice, explores the root causes of consensus deficiency, and discusses the function of social dialogue in news practice. The article further starts from two aspects: the construction of conceptual consensus and the construction of innovative models, clarifying effective ways to enhance news consensus in news practice, aiming to provide reference and inspiration for future news practice.